Customers' willingness to share personal information with firms and its relationship with customer loyalty - Lindell, Sanni (2015)
Information on customers plays an important role in customer relationship management. With customer data companies can identify customers, understand their needs and hence, personalize products and services. New technological advancements have enabled companies to collect data more efficiently and have therefore resulted in broader use of information. However, customers must be willing to provide information needed in CRM. If trust has been built, they might provide information and engage in mutual relationship. Even though customer’s willingness to provide information is an important issue for companies, little research has been devoted to this phenomenon. The objective of this research is to gain more insight of customer’s willingness to share information by inspecting how the willingness affects the commonly used loyalty metrics (share of wallet, recommend intention, repurchase intention) as well as customer’s RFM value (recency, frequency and monetary value of purchases). This study was conducted in cooperation with Osuuskauppa PeeÄssä and Kuopio’s Prisma grocery store. A quantitative research method was used by conducting the electronic survey in Kuopio’s Prisma’s Facebook –page as well as Osuuskauppa PeeÄssä’s webpage. The data of 429 responses was analyzed by using SPSS statistics and PLS 3.0 software. The results of this study indicate that customer’s willingness to provide information has a significant and positive effect on commonly used loyalty metrics; customer’s repurchase intention, recommend intention and share of wallet. In addition SOW positively affects customer’s repurchase and recommend intention and customer’s RFM value. Also recommend intention has a positive effect on customer’s RFM value. Finally, customer’s willingness to share information positively affects RFM value indirectly via above mentioned loyalty metrics. The findings suggest that marketers should increase customer’s willingness to share information as it, in fact, positively affects the level of customer’s loyalty and value. Information should be used in a more customer centric way where additional value is created to the customer.